2000
DOI: 10.1027//0269-8803.14.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Variations in Body Hydration on Cognitive Function

Abstract: Eight healthy men, unacclimated to heat, were submitted to variations in body hydration. The subjects were kept euhydrated, dehydrated by controlled passive hyperthermia or exercise on a treadmill up to a weight loss of 2.8%, or hyperhydrated using a solution containing glycerol, with a total ingested volume equal to 21.4 ml/kg of body weight. On completion of a 90-min recovery period, the subjects were assigned a pedaling exercise on an arm-crank ergometer. Psychological tests were administered 30 min after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(52 citation statements)
references
References 15 publications
0
44
0
Order By: Relevance
“…Attention can be subdivided in selective, divided, and sustained attention functions, whereas executive functions encompass more complex processes such as reasoning, planning, concept formation, evaluation, and strategic thinking. 22 Research in our laboratory and others supports the hypothesis that mild dehydration produces alterations in a number of important aspects of cognitive function such as concentration, alertness, and short-term memory in young adults 18 to 25 years of age [23][24][25][26][27] and in the oldest adults 50 to 82 years of age. 28 Most of the cited studies were randomized, controlled trials.…”
Section: Hydration and Cognitive Functionmentioning
confidence: 55%
“…Attention can be subdivided in selective, divided, and sustained attention functions, whereas executive functions encompass more complex processes such as reasoning, planning, concept formation, evaluation, and strategic thinking. 22 Research in our laboratory and others supports the hypothesis that mild dehydration produces alterations in a number of important aspects of cognitive function such as concentration, alertness, and short-term memory in young adults 18 to 25 years of age [23][24][25][26][27] and in the oldest adults 50 to 82 years of age. 28 Most of the cited studies were randomized, controlled trials.…”
Section: Hydration and Cognitive Functionmentioning
confidence: 55%
“…On the other hand, no particular effects for body composition variables were seen on cognitive domains, probably masked by other, predominant contributions, similarly to what reported during the Tor des Géants (Tonacci et al, 2016). This particular comparison was rarely performed among athletes, even though it was demonstrated that exercise-induced dehydration severely affects cognitive function (Cian et al, 2000). The findings reported by Cian et al (2000) were referring, however, to dehydrated athletes, while none of our athletes had experienced dehydration as showed by the TBW composition.…”
Section: Discussionmentioning
confidence: 99%
“…This particular comparison was rarely performed among athletes, even though it was demonstrated that exercise-induced dehydration severely affects cognitive function (Cian et al, 2000). The findings reported by Cian et al (2000) were referring, however, to dehydrated athletes, while none of our athletes had experienced dehydration as showed by the TBW composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During these stays, they must often be rapidly operational, despite substantial heat stress that can be induced by clothing that impedes heat loss (battledress), the physical work rate (endogenous heat production), and most of all, the environmental conditions (temperature, humidity, or solar radiation) in these areas. These conditions increase physiological strain, reducing physical (Périard et al, 2015; Székely et al, 2015), cognitive, and psychomotor performance (Cian et al, 2000; Hancock et al, 2007), and increasing the occurrence of exertional heat illnesses, such as exertional heat stroke (Pryor et al, 2015), diseases that are common in worker populations (Marchetti et al, 2016) and especially soldiers (Armed Forces Health Surveillance Bureau, 2017). This problem was recognized more than 200 years ago when Europeans arriving in tropical climates did not adapt their working behaviors and eventually faced heat illnesses (Lind, 1771; Jackson, 1795; Taylor, 2014).…”
Section: Introductionmentioning
confidence: 99%